INTEGRASI PEMILIH BERINTEGRITAS NEGARA KUAT PADA LINGKUP MASYARAKAT LUBUK TILAN DAYUN KABUPATEN SIAK - Alexsander Yandra; Andrizal Andrizal; Adrian Faridhi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Direct General Election by the public is a transfer of power and power competition, and a means of democracy in the embodiment of people's sovereignty in order to produce leaders as mandated in the Law. However, elections tend to be interpreted as a five-year procedural democracy that does not have a positive impact on people's lives. On the basis of these considerations, political education and civic culture in the community can encourage the political culture of participants and the culture of a democratic society, which is why these community service activities are made. This activity will be focused on Kampong Lubuk Tilan, Dayun District, Siak, where people are still not politically literate. Lubuk Tilan area is an urban, remote area where transactional political resistance and money politics often occur. For this reason, service is carried out in the form of political education and guidance by providing materials that can encourage and enrich people's knowledge related to ethical political values. This education and guidance will be in the form of lectures, discussions and supervisory technical guidance (checks and balances). This political and civic culture education will be provided by teaching staff who are experts in the fields of politics, law, citizenship and elements of regional election organizers, namely the KPU, especially the socialization division